Voices from the Pulpit: Islamic Religious Leaders’ Perspectives on Green Open Space Corruption and Their Prevention Efforts in Bandung - Hermawan, Ucep; Shamsu, Lilly Suzana binti Haji (Hanifiya: Jurnal Studi Agama-Agama, 2024)
This article examines the views of Islamic religious figures regarding the Green Open Space (RTH) corruption case in Cisurupan Village, Cibiru District, Bandung City, as well as their role in preventing similar corruption. Considering that the majority of Cisurupan residents are Muslim, this research highlights the views of religious figures from various backgrounds. Qualitative research methods with a field study approach were used. Data was collected through in-depth interviews with four religious figures who play a role in society, education, MUI, and government, as well as secondary data from literature and internet sources. Data analysis compares interview results with literature to understand the perceptions and role of religious figures in RTH corruption cases. The research results show that religious figures' views on corruption vary. Some consider corruption a religious violation due to a lack of understanding of religious teachings, while others see it as a personal choice influenced by individual and environmental factors. The role of religious figures in preventing corruption includes moral education, anti-corruption outreach, and education on the values of honesty in schools. The conclusion of this research shows that the views and roles of religious figures are greatly influenced by their social background, personal experiences and position in society. This research provides insight into the perceptions and roles of Islamic religious leaders in preventing corruption in Muslim-majority areas. It is recommended that further research involve more religious figures for a more comprehensive understanding.